2010
DOI: 10.1038/npp.2010.192
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Antimanic Treatments: Meta-analysis of Randomized, Controlled Trials

Abstract: We conducted meta-analyses of findings from randomized, placebo-controlled, short-term trials for acute mania in manic or mixed states of DSM (III-IV) bipolar I disorder in 56 drug-placebo comparisons of 17 agents from 38 studies involving 10 800 patients. Of drugs tested, 13 (76%) were more effective than placebo: aripiprazole, asenapine, carbamazepine, cariprazine, haloperidol, lithium, olanzapine, paliperdone, quetiapine, risperidone, tamoxifen, valproate, and ziprasidone. Their pooled effect size for mania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
174
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(189 citation statements)
references
References 69 publications
9
174
2
4
Order By: Relevance
“…Recently two meta-analyses concerning medication in acute mania were published, one of them in Neuropsychopharmacology (Tarr et al, 2011;Yildiz et al, 2011). Both of them report an analysis of change vs initial severity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently two meta-analyses concerning medication in acute mania were published, one of them in Neuropsychopharmacology (Tarr et al, 2011;Yildiz et al, 2011). Both of them report an analysis of change vs initial severity.…”
mentioning
confidence: 99%
“…In one of them, the authors reported a significant relationship between change in raw YMRS score and baseline raw YMRS score for all treatment arms combined (Tarr et al, 2011). However, in the second one, the authors used Hedges' g effect size vs baseline score as percentage of maximum, and reported that higher baseline mania ratings predicted greater improvement with drug but not with placebo (Yildiz et al, 2011). The meta-analytic studies on unipolar depression suggested that medication might not work for mildly depressed patients and hence they should not be prescribed, and as similar findings and conclusions seem to emerge from the meta-analysis of acute mania trials, it seems important to tackle again this issue.…”
mentioning
confidence: 99%
“…Pharmacological therapy is often the first-line treatment for BD, followed by psychological (Oud et al, 2016) and psychosocial interventions (Goodwin et al, 2008). In addition to lithium and anticonvulsants (van der Loos et al, 2011;Yildiz et al, 2015), antipsychotic agents have also shown promising efficacy for bipolar mania (Yildiz et al, 2011) and depression (Goodwin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of improvement in mania ratings, atypical antipsychotics seem to yield greater effect size than mood stabilizers, although overall efficacy of atypical antipsychotics does not differ clinically from haloperidol. Despite the compelling antimanic efficacy of haloperidol, typical antipsychotics are no longer commonly used to treat acute mania, owing to their unfavorable risk for shortand long-term adverse effects, although these need to be balanced against considerable long-term adverse metabolic effects of some atypical antipsychotics (Yildiz et al, 2011).…”
mentioning
confidence: 99%